Respuestas
Respuesta dada por:
67
4(2x)-3(3x-5)=12x-180
8x-9x+15=12x-180
-x+15=12x-180
13x= 195
x=195/13
x= 15
8x-9x+15=12x-180
-x+15=12x-180
13x= 195
x=195/13
x= 15
Respuesta dada por:
34
Despejando la variable "x"
4 ( 2x ) - 3 ( 3x - 5 ) = 12x - 180
8x - 9x + 15 = 12x - 180
- x - 12x = - 180 - 15
-13x = - 195
x = -195/-13
x = 15 → Solución
4 ( 2x ) - 3 ( 3x - 5 ) = 12x - 180
8x - 9x + 15 = 12x - 180
- x - 12x = - 180 - 15
-13x = - 195
x = -195/-13
x = 15 → Solución
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años